Effects of Psychosocial Stress, Neuroticism Liability and Unhealthy Coping Strategies on the Physical and Mental Welfare of Pre-University Students in the National University of Malaysia - a/p Joseph Thomas, J. Soosiamaal; a/p Annadurai, Priyadiana (Journal of Social Transformation and Regional Development, 2021)
Stress is the body’s response to changes that create taxing demands. Coping mechanism plays a significant part to overcome or reduce the stress experienced by individuals. The purpose of the study is to study the relationship between psychosocial stress, neuroticism liability and unhealthy coping strategies on the physical and mental welfare of pre-university students. One hundred and forty four pre-university students from the National University of Malaysia are included in this study. A quantitative study utilizing a cross sectional non-probability sampling research design is used to gather data. The data is collected using a questionnaire which analyzes three main aspects of this study namely, psychosocial stress, neuroticism liability and unhealthy coping mechanisms. The instruments used to measure psychosocial stress is the individual items of the University Students Stress Scale .The unhealthy coping strategies will be assessed by the Brief COPE Inventory through the ordinal data (individual survey items) obtained. However, neuroticism liability will be measured through the Eysenck Personality Inventory. The SPSS Statistics Data Editor Version 25 is used for statistical analysis. In conclusion, all three variables are correlated with each other. When a person experiences immense psychosocial stress, the person tends to inculcate more unhealthy coping strategies in daily lives and it may contribute to increasing neuroticism liability.